Effects of L-Carnitine and Coenzyme Q10 on Impaired Spermatogenesis Caused by Isoproterenol in Male Rats - Ghanbarzadeh, S.; Garjani, A.; Ziaee, M.; Khorrami, A. (Drug Research, 2014)
Nowadays, cardiovascular diseases and male infertility are two big health problems in industrial countries.The aim of the present study was to investigate the protective role of coenzyme Q10 and L-Carnitine pretreatment in the impaired spermatogenesis caused by isoproterenol (ISO) in male rats.Thirty-two male Wistar rats were allocated in 4 groups. ISO was injected for 2 consecutive days (100 mg/kg) in ISO treated groups. Before ISO administration, pretreatment with Coenzyme Q10 (10 mg/kg/day) and L-Carnitine (350 mg/kg/day) were conducted for 20 consecutive days. Sex hormones level, malondialdehyde (MDA) and total antioxidant concentration as well as testis, epididymis and seminal vesicle weight were investigated.Increase in the concentration of MDA and decrease in total antioxidant level was observed following ISO administration. Accordingly, the sperm viability as well as testis, epididymis and seminal vesicle weights were decreased. In the case of sex hormones, the testosterone and LH levels were decreased and the concentration of FSH was increased. Pretreatment with L-carnitine and Coenzyme Q10 significantly decreased the MDA level and increased total antioxidant, LH and testosterone levels. Pretreatment with L-carnitine and Coenzyme Q10 also improved semen parameters and organs weight which were impaired by ISO administration.L-carnitine and Coenzyme Q10 pretreatment could protect spermatogenesis in male rats with ISO administration.
Keywords: spermatogenesis; isoproterenol; myocardial infarction; L-carnitine; coenzyme Q10